ChemInform Abstract: K3MoPO7: The First Molybdenum Phosphate with Edge‐Sharing MoO6 Octahedra and PO4 Tetrahedra. Issue 48 (2nd December 2014) - Luo, Siyang; Kang, Lei; Lin, Zheshuai; Chen, Chuangtian
Abstract The new title compound is synthesized by melting a stoichiometric mixture of K2CO3, MoO3, and K2HPO4 followed by slow cooling.